Diasporic Identities in Bharati Mukherjee’s Jasmine - Adhikari, Baldev (Mindscape: A Journal of English & Cultural Studies, 2025)
This paper analyzes the formation of Jasmine’s fluid identities as her survival strategies in Bharati Mukherjee’s novel Jasmine. While doing the textual analysis, theoretical notions like cultural identities, diasporic identities, and the concept of ‘third space’ are used as analytical tools in this article. In the process of her transformative journey, the young Indian female immigrant encounters cross-cultural challenges and complexities in the new world. She gradually adapts to different social and cultural landscapes of the American society and navigates a series of new identities. As a flexible immigrant, Jasmine develops her hybrid identities while living in diasporic locations in America. Initially Jasmine embodies a space of cultural negotiations and hybridity. Then she transcends the space of in-betweenness. She possesses a dynamic and evolving character. She is ever-changing according to the situation of new environments. She undergoes multiple identity transformations to locate herself in the American society. Her identity is formed according to the changes in her name from Jyoti to Jasmine to Jazzy to Jane. As a diasporic woman, she performs different facets of her multiple identities to situate and survive in the American society. Finally, the docile Indian widow turns into an independent active modern American woman. Due to her fluid identities, Jasmine is empowered and successfully transforms and assimilates into American culture. Jasmine survives in new diasporic locations because she moves forward courageously and independently.